Engineering geology - Cox, Dave (Magnum Publishing, 2016)
Engineering geology is the application of the geological sciences to engineering study for the purpose of assuring that the geological factors regarding the location, design, construction, operation and maintenance of engineering works are recognized and accounted for. Engineering geology studies may be performed during the planning, environmental impact analysis, civil or structural engineering design, value engineering and construction phases of public and private works projects, and during post-construction and forensic phases of projects. This book covers the fields of the earth sciences and engineering, particularly geological and geotechnical engineering. The focus of the book is on geological or engineering studies that are of interest to engineering geologists.